VALIDATION OF PROCESS SAFETY CULTURE MODEL USING DELPHI METHOD - AHMED AHMED AL-AWADHI, KHOBAIB (IRC, 2017)
Over the previous three decades’ scientists have struggle on discovering what safety culture is and what key elements make up a safety culture. Nevertheless, there is no consent extended with regards to validation of safety factors. For this purpose, a validation of process safety culture model using DELPHI method are developed for the justification of the safety culture key factors model. A validation of process safety culture factor model using DELPHI method is developed and used as a nominee model using methodical literature review. A validation survey questionnaire will be used and will target various industries and experts. Findings from this study are a validation of the key factors model of safety culture, and a development of safety culture survey as a verification tool for the developed model. Verdicts of this study will assist to improve the safety culture and practices in the industries in Malaysia. Up-to-date none of the studies has been testified on the validation of factors model for safety culture. The DELPHI questionnaire developed has the potential to develop a systematic safety culture model in order to reduce adverse safety issues impact.